Kerjasama dan Komunikasi Interpersonal dalam Penanganan Masalah Kesehatan Mental dengan Memperhatikan Keselamatan Pasien - Aulia Rani; Arum Dwi Anjani; Devy Lestari Nurul (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine interpersonal cooperation and communication in handling mental health problems by paying attention to patient safety. This research is a type of descriptive qualitative research that uses metadata analysis techniques through literature review. In research, a literature review refers to the analysis and integration of literature relevant to the research topic. This is an important component of research that is often considered a solid foundation for high-quality scientific work. The results of this study show that every health service in a hospital needs to pay attention to patient safety. Medical procedures given to patients have risks that can cause pain, disability or death. Risks in health services can result from errors in the system. Generally, infections after surgery or nosocomial infections occur due to errors in the nursing system such as lack of risk management and undetected resistant bacteria.